Thinking about Kindergarten thinking: A mixed methods study - Braund, Heather (Frontiers in Psychology, 2022)
Metacognition, otherwise known as ‘thinking about one’s thinking’ leads to greater academic success and is foundational. Given this importance, metacognitive behaviours need to be developed within early years contexts to provide young children the opportunity to practice these behaviours and receive feedback. However, literature continues to focus on the development of metacognition in later grades. This mixed methods study explored metacognition in eight Kindergarten classrooms. Participants included eight Kindergarten teachers, six early childhood educators (ECEs), and 80 students. Data collection was conducted at two time periods separated by twelve weeks. Data collection included the Children’s Independent Learning Development (CHILD) measure, semi-structured interviews, and classroom observations. The quantitative data from the CHILD were analyzed using a paired samples t-test in SPSS. All qualitative data were analyzed thematically. Qualitatively, three themes were identified: 1) Conceptualization of metacognition, 2) Barriers to developing metacognition, and 3) Operationalization of strategies to facilitate metacognitive development. Evidence demonstrated that participants had incomplete conceptualizations of metacognition. Some articulated simple understandings by reporting the literal translation and were unable to articulate more fulsome conceptions. However, some teachers had more developed conceptions of metacognition that included different facets such as planning and reflective thinking. All participants were forthcoming with identifying ways in which they struggled with implementing metacognitive practices or encouraging the development of metacognition. These barriers included large classroom sizes, developmental readiness, and wide student ability. Despite having incomplete understandings of metacognition, early years educators were trying a variety of different strategies to help promote metacognitive thinking within their Kindergarten classrooms. Surprisingly, teacher ratings using the CHILD did not change significantly from Time 1 (M=1.88, SD=.744) to Time 2 (M=1.85, SD=.66), t (72) = .72, p > .05. A similar trend was observed for ECE ratings using the CHILD as they did not change significantly from Time 1 (M=1.89, SD=.70) to Time 2 (M=1.80, SD=.79), t (52) = 1.36, p > .05. This research highlights empirical practices that Kindergarten educators can use to help facilitate metacognitive thinking. Further, it identifies a need to better support Kindergarten educators with developing metacognitive thinking in their students through explicit examples of strategies.